MRI-Based Estimation of Scalar Cochlear-Implant Electrode Position. (17th October 2017) - Stratmann, A.; Mittmann, P.; Rademacher, G.; Grupe, G.; Hoffmann, S.; Mutze, S.; Ernst, A.; Todt, I.
Abstract : The position of the cochlear-implant electrode is important to audiological outcomes after cochlear implantation. The common technique to evaluate the intracochlear electrode's position involves the use of ionized radiation in MSCT, DVT, or flat-panel tomography (FPT). Recent advances in knowledge regarding the handling of MRI artifacts in cochlear implantees indicate that estimating the intracochlear electrode's position with an MRI could be possible. This study's aim was to evaluate the ipsilaterally position of electrodes using MRI at 1.5 T. In a retrospective study of 10 implantees with postoperative need for MRI scanning, we evaluated the intrascalar electrode's position using a T2-weighted sequence at 1.5 T. We compared the resulting estimate of the intracochlear position with the estimates from the postoperative FPT scan and the intraoperative NRT ratio. For each ear, the MRI-estimated scalar position corresponded with the estimated positions from the FPT and NRT ratio. For eight ears, a scala tympani's position was observed in the MRI. In one case, an electrode scalar translocation was found. In one case, the scala vestibuli's position was observed. Thus, MRI-based estimation of the scalar position of a cochlear-implant electrode is possible. Limitations to this method include implant-specific magnet and fixation configurations, which can cause complications.